Interference film grown on stainless steel by pulsed current process using chromium free vanadate solution - Junqueira,Rosa Maria (2018)
ABSTRACT Deposition of interference film is an alternative way for the formation of colored protective layers on the surface of stainless steels for decorative applications. The process involves growth of a chromium oxide film by electrochemical methods using in general sulphochromic solutions. However, it is well known that chromic acid contains Cr(VI), which is highly toxic, demanding special effluent treatments in order to avoid environmental pollution. The aim of the present work is to evaluate alternative chromium free solutions for coloration of stainless steel by an electrochemical method as a trial to avoid the Cr(VI) presence to achieve an environmentally friendly process. The morphology and corrosion resistance of the conversion coatings obtained from sodium vanadate solution were comparatively evaluated with a sample coloured in a sodium molybdate solution containing chromium and in a sulfochromic solution currently used in industrial coloration process. The corrosion behaviour of the colored samples was evaluated by using anodic potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The steel colored in a solution containing chromium and molybdenum ions showed the lowest corrosion resistance and a more porous and heterogeneous film than the other steel samples colored using vanadate and sulfochromic solutions. An electrochemical processing using a sodium vanadate solution can be a chromium free alternative for industrial application.